2006
DOI: 10.1094/phyto-96-0900
|View full text |Cite
|
Sign up to set email alerts
|

An Indigenous Virulent Strain of Erwinia amylovora Lacking the Ubiquitous Plasmid pEA29

Abstract: An atypical strain of Erwinia amylovora was isolated near an outbreak of fire blight at a nursery in Spain in 1996. It was obtained from a Crataegus plant showing typical symptoms and was identified as E. amy-lovora by biochemical tests and enrichment-enzyme-linked immuno-sorbent assay, but not by polymerase chain reaction using primers based on the pEA29 sequence. Nevertheless, with primers from chromosomal regions, the isolate gave the expected amplification band. This strain carries one plasmid of approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 47 publications
2
47
0
Order By: Relevance
“…On diagnosis, this result shows that only the primers as pEA71, EaIsc are reliable. In addition, other strain of fire blight reported absence of plasmid pEA29 [24], [25].…”
Section: Discussionmentioning
confidence: 99%
“…On diagnosis, this result shows that only the primers as pEA71, EaIsc are reliable. In addition, other strain of fire blight reported absence of plasmid pEA29 [24], [25].…”
Section: Discussionmentioning
confidence: 99%
“…in Spain and is obviously related to strain IVIA1614-2a, which was isolated from Crataegus sp. and also described as lacking plasmid pEA29 (Llop et al 2006). Isolation of these strains without pEA29 from different sites or from different host plants supports their natural existence.…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally, the transposon was delivered into pEA29 visible by band shifts in plasmid fragments and created a convenient label in the plasmid for genetical manipulations. Additional plasmids have been described for E. amylovora, and a 70 kb plasmid was assumed to compensate for a lack of pEA29 (Llop et al 2006). In this study, we screened E. amylovora strains from various geographic origins for the presence of pEA29 and describe strains, where neither pEA29 nor any other plasmid could be detected.…”
Section: Introductionmentioning
confidence: 99%
“…Such a reaction may indicate an earlier acquisition of pEA29 from E. amylovora. By contrast, a few isolates of E. amylovora without this plasmid were found in Egypt, Iran, Spain and the USA (Carey et al 2011;Llop et al 2006;Mohammadi et al 2009). Also, it was found that another plasmid of approximately 65 kb (pEI70) present in one of these isolates, showed no homology with pEA29.…”
Section: Analysis Of Nucleic Acidsmentioning
confidence: 95%